Growth and mortality of green mussel, Perna viridis in the high spat-fall areas of Marudu Bay and Ambong Bay, Sabah, Malaysia - Ong, Fang Sing (2018)
Present study was conducted with the aim to understand the growth performance of green mussel, Perna viridis in two high spat-fall areas on the west coast of Sa bah, Malaysia: Marudu Bay and Am bong Bay, by comparing environmental parameters data with growth data. The three selected study sites, which included river mouth station (Marudu Bay), coastal and open sea stations (Ambong Bay) could help to understand the favourable and suitable environmental conditions for better growth performance of green mussels. Samplings were carried out once a month for 12 months period (October 2015 - September 2016). The results showed the growth parameters of green mussel in coastal station have the highest increment, with 3.15cm in shell length, 11.23g in live weight, 2.37g in wet meat weight, 0.23g in dry meat weight, and 0.16g in ash free dry meat weight. The growth increments were significantly higher (p<0.05) in coastal than river mouth and open sea stations. The mussels cultured in the river mouth station attained highest mean meat yield (28.67%) but also recorded the highest cumulative mortality with 6.48%. In contrast, mussels in coastal and open sea stations recorded 1.48% and 2.96% respectively. Cumulative mortality of mussels in all stations showed significant different (p<0.05). Phytoplankton and zooplankton conc entrations in the three stations showed no significant difference (p>0.05). However, coastal and open sea stations were found to have dominated by potential harm ful algae ( Chaetoceros spp. and Prorocentrum spp.). Overall, growth parameters in all stations showed negative correlation with salinity, temperature, DO and chlorophyll-a. Meat yield and condition index were positively correlated with chlorophyll-a, TPM and PIM in all stations. Water current speed in coastal and open sea stations were positively correlated with the growth parameters, but negatively correlated in river mouth station. pH showed to have positive correlation with the growth parameters in open sea station but only positive correlation with dry meat weight and ash free dry meat weight in coastal station. Phytoplankton cell dens ity was found negatively correlated with meat yield in river mouth and open sea station but positively correlated in coastal station. On the other hand, zooplankton density was positively correlated with meat yield in river mouth and coastal station but negatively correlated in open sea station. In conclusion, green mussels in Ambong Bay (coastal station) exhibited better growth performance in term of shell length and live weight but lower meat yield, which are unfavourable to consumers. Green mussels in Marudu Bay (river mouth station), on the other han d, exhibited higher meat content but also experienced higher mortality rate, which is unfavourable by farmer. The higher mortality of mussels in Marudu Bay warr ant furt her investigation on factors other than food availability and environmental conditions, such as predation and disease.